Effect of Hydroxyapatite on Microstructure and Hardness of Mg-Al-Zn Alloy - Andy Saputro; Intan Khoerunisa; Kusharjanto Suhirman; Supono Adi Dwiwanto (Jurnal Metalurgi dan Material Indonesia, 2018)
This paper focused on microstructure and hardness of Mg-Al-Zn alloy by Hydroxyapatite addition. Mg-Al-Zn alloys were prepared by casting with the addition of Hydroxyapatite from 1,5% to 2,5%wt, then water quenched. The microstructure evolution and hardness were investigated. The result showed that increasing of Hydroxyapatite content made the globular and smaller grains. Based on hardness test result the hardness was increased. With 1,5% to 2,5% Hydroxyapatite addition, hardness increased from 75.52 HV to 82.82 HV. The highest hardness was in the addition of 2.5% Hydroxyapatite with 82.82 HV.